Medical Student Ultrasound Education: The Radiology Chair Weighs In. Issue 1 (March 2021) - Sohaey, Roya; Di Salvo, Donald N.; Bluth, Edward I.; Lockhart, Mark E.; Cohen, Harris L.; Pellerito, John S.; Baltarowich, Oksana H.; Nisenbaum, Harvey L.; Coleman, Beverly G.
Abstract: To assess the radiology department chairs' opinions concerning current status and plans for teaching ultrasound to medical students, the American College Taskforce on Radiology Ultrasound Education, commissioned by the American College of Radiology, distributed a survey to 142 radiology chairs and a medical school dean subgroup. The response rate was 30% (42/142), and 76% indicated ultrasound was currently part of the medical student curriculum. In preclinical years, radiology involvement was only 6.4%. During clinical years, radiology led ultrasound education with 51.7% in general and 82.9% in elective rotations. Regarding actual content, top 4 results were evenly distributed between learning hands-on scanning (81.1%), diagnostic use of ultrasound (75.7%), anatomy/pathology (75.7%), and ultrasound guidance for procedures (54.0%). Educational leaders in preclinical courses were emergency medicine (72.7%) followed by radiology (45.4%) physicians. During clinical years, leaders were radiology (52.6%) and emergency medicine (47.4%) physicians. Most chairs stated that knowledge of diagnostic ultrasound should be mandatory (76.2%), stressing the importance of teaching the diagnostic capabilities and uses of ultrasound as the primary goal (78.8%). Perceived barriers to implementation were evenly distributed between lack of space in the curriculum (55.6%), lack of faculty (48.2%), lack of resources (44.4%), and lack of institutional support (40.7%). The American College Taskforce on Radiology Ultrasound Education survey shows that radiology's role in ultrasound undergraduate education occurs almost exclusively during clinical years, and the chairs voice a desire to improve upon this role. Barriers include both intradepartmental (faculty and resources) and institutional (curricular) factors.